1980
DOI: 10.1136/pgmj.56.657.478
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effect of cimetidine and ranitidine on prolactin secretion

Abstract: SummaryCimetidine has been shown to stimulate prolactin secretion after intravenous administration. Cimetidine 200 mg and ranitidine 50 mg was given i.v. in a randomly allocated order to 22 volunteers on consecutive days; these doses can be regarded as equivalent as far as inhibition of gastric acid output is concerned. Plasma prolactin was estimated at regular intervals. The prolactin stimulating effect of cimetidine was confirmed while ranitidine did not influence plasma prolactin levels.Although cimetidine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…These findings supported the observations of Bateson et al, 18 Burland et al, 4 Carlson et al, 19 Winter et al, 20 Penden et al 21 and Nelis et al 6 The prolactin levels in pretreated rabbits were found insignificantly raised on statistical analysis (Diagram).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These findings supported the observations of Bateson et al, 18 Burland et al, 4 Carlson et al, 19 Winter et al, 20 Penden et al 21 and Nelis et al 6 The prolactin levels in pretreated rabbits were found insignificantly raised on statistical analysis (Diagram).…”
Section: Discussionsupporting
confidence: 85%
“…4,5 The rise in prolactin secretion after IV Cimetidine is widely agreed, but the mechanism of action is still unclear. 6 Even though there were many reports of raised prolactin level with many side effects, 7 only a few case of raised prolactin level is related with Cimetidine administration. 8 But the effect of the newer H2 receptor antagonists Ranitidine does not produce the rise in serum prolactin level even after IV Ranitidine.…”
mentioning
confidence: 99%
“…The anti-andro¬ genic effect of cimetidine therefore appears to be an inherent property of this compound and is not related to its histame H2-receptor blocking activity. Similarly, Nelis & Van de Meene (1980b) have shown that while intravenously administered cime¬ tidine stimulates prolactin secretion, ranitidine does not, thus providing another example of dis¬ sociation between histamine H2-receptor blocking activity and the endocrine effects of these drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Cimetidine has been shown to affect the hepatic metabolism of a number of drugs including antipyrine and aminopyrine (Staiger et al, 1980;Henry et al, 1980), warfarin and phenindione (Hetzel, Birkett and Miners, 1979), chlordiazepoxide and diazepam (Patwardham et al, 1980), phenytoin (Hetzel et al, 1981) and propranolol (Heagerty et al, 1981). In addition, cimetidine produces an elevation of serum prolactin levels after intravenous injection (Nelis and Van de Meene, 1980;Kleist et al, 1981). Ranitidine has been reported as showing more prolonged gastric acid suppression than cimetidine in a man with Zollinger-Ellison syndrome in whom gynaecomastia regressed and sexual activity improved when ranitidine was substituted for cimetidine (Mignon et aL, 1980).…”
Section: Discussionmentioning
confidence: 99%